Protection of Heirs' Rights from the Actions of a Patient in Their Final Illness in Islamic Sharia and French Law: A Comparative Study - Abdulghani Abuishkewa (International Journal of Law Research and Studies, 2025)
This study examines the restrictions imposed on the dispositions of a terminally ill patient to safeguard the rights of heirs, comparing Islamic law and French law. In Islamic jurisprudence, terminal illness limits financial capacity, prohibiting donations exceeding one-third of the estate without the consent of the heirs to ensure equitable inheritance distribution. Scholars differ on whether the determination of terminal illness should rely on medical diagnosis or psychological impact. In contrast, French law does not recognize a specific concept of terminal illness but focuses on the soundness of will, allowing challenges to gifts and wills if mental incapacity is established. Additionally, it imposes legal restrictions to protect reserved heirs and maintain a balance between testamentary freedom and inheritance rights, reflecting a common objective despite differing legal foundations.
Keywords: Terminally Ill Patient; Heirs' Rights; Islamic Law; French Law; Financial Capacity; Donations; One-Third of the Estate; Equitable Inheritance Distribution; Medical Diagnosis; Psychological Impact; Soundness of Will; Gifts and Wills; Reserved Heirs; Freedom of Disposition; Inheritance Protection